Ultrasound-Guided Transversus Abdominis Plane Block versus Land Mark Technique in Lower Abdominal Surgery - Khaskheli, Muhammad Saleh; Tabassum, Rafia; Awan, Aijaz Hussain; Imtiaz, Almas; Shah, Salamullah; Baloch, Zaigham din (Journal of Liaquat University of Medical & Health Sciences, 2022)
Objective: To determine the efficacy of pain for Ultrasound-Guided Transversus Abdmominis Plane Block versus landmark technique in lower abdominal surgery. Methodology: This Randomized Control trial study was conducted from July to December 2018 at the Department of Anesthesiology, Peoples Medical University & Hospital Shaheed Benazirabad. The sample techniques were used randomly through envelopes, and the sample size was 120. Results: The study findings revealed that age distribution among L and U groups regarding gender was 70% females 66.7% females. Moreover, for ASA status in the L group, 58.3% of the participants stand in 2-4 ASA status, whereas in the U group, 50% of the participants were in ASA status 1 and 2-4 each. The bilateral block was performed among 85% of the participants in the L group and 96.7% of the participants in the U group. In the surgical procedure in the L group, 15% underwent appendectomy, whereas, in the U group, 28.3% underwent lower c- section. The overall rate of postoperative pain at 60 minutes was observed in 10 women among both groups. Statistically significant results among both groups with a p-value of 0.001. Conclusion: Our study results showed that surgeries performed using Ultrasound-Guided Transversus Abdominis Plane Block are more effective with less postoperative analgesia. KeyWords: Efficacy, Ultrasound Guided Tranversus Abdominis Plane Block, landmark technique, Lower Abdominal Surgery, Anesthesia, TAP block